2019
DOI: 10.1159/000497454
|View full text |Cite
|
Sign up to set email alerts
|

The Preoperative Prognostic Nutritional Index Predicts Short-Term and Long-Term Outcomes of Patients with Stage II/III Gastric Cancer: Analysis of a Multi-Institution Dataset

Abstract: Background/Aims: Identification of nutritional indicators to predict short-term and long-term outcomes is necessary to provide appropriate treatment to patients with gastric cancer. Methods: We designed an analysis of a multicenter dataset of patients with gastric cancer who underwent gastrectomy between 2010 and 2014. We enrolled 842 eligible patients who had stage II/III gastric cancer. The area under the curve (AUC) values were compared among prognostic nutritional index (PNI), calculated as 10 × albumin g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…In addition to the effects of poor oral nutritional intake and protein loss from the primary lesion, cancer cells secrete cytokines, such as tumor necrosis factor-alpha, which adversely affect catabolic metabolism [27][28][29][30][31]. Malnutrition renders patients more susceptible to infection, prolongs wound healing, and increases the risk of postoperative complications [32][33][34][35]. Thus, a proper preoperative assessment of the nutritional status of gastric cancer patients should be performed.…”
Section: Nutritionmentioning
confidence: 99%
“…In addition to the effects of poor oral nutritional intake and protein loss from the primary lesion, cancer cells secrete cytokines, such as tumor necrosis factor-alpha, which adversely affect catabolic metabolism [27][28][29][30][31]. Malnutrition renders patients more susceptible to infection, prolongs wound healing, and increases the risk of postoperative complications [32][33][34][35]. Thus, a proper preoperative assessment of the nutritional status of gastric cancer patients should be performed.…”
Section: Nutritionmentioning
confidence: 99%
“…The correlation of the indicators reflecting nutritional status with survival in patients with various types of cancer has received much attention in recent years [14][15][16] . Cancer-related malnutrition is frequently caused by activation of systemic inflammation due to cancer progression, resulting in impaired immunity and reduced survival 8,11,17 . Furthermore, patients with advanced ovarian cancer frequently experience malnutrition due to peritoneal dissemination associated with bowel obstruction 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of the clinical indicators that predict long-term outcomes is needed to improve the management of patients with early-stage OCCC.Malnutrition has been reported to make patients more susceptible to infection, increase the risk of postoperative complications, and promote tumor recurrence through suppression of tumor immunity 6-8 . The prognostic nutritional index (PNI), which is calculated using serum albumin level and lymphocyte count as indicators of nutritional status, has been reported to be correlated with survival and perioperative complications in various types of cancer [8][9][10][11] . Even in gynecologic malignancies, low PNI was recently reported to be associated with poor prognosis in HGSOC and cervical cancer 12,13 .…”
mentioning
confidence: 99%
“…For example, in gastric cancer, a lower PNI was associated with a more aggressive tumor, higher recurrence, poor overall survival, and higher risk of postoperative complications. [6][7][8] Moreover, some authors have suggested the optimal cut-off value of the PNI for predicting the survival of patients with gastric cancer. [7] However, the PNI values are not widely used in clinical practice for gastric cancer because the aggressive nature of the tumor and the need for adjuvant chemotherapy followed by surgery were important factors that resulted in better survival and the association between nutritional status and tumor aggressiveness is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Moreover, some authors have suggested the optimal cut-off value of the PNI for predicting the survival of patients with gastric cancer. [7] However, the PNI values are not widely used in clinical practice for gastric cancer because the aggressive nature of the tumor and the need for adjuvant chemotherapy followed by surgery were important factors that resulted in better survival and the association between nutritional status and tumor aggressiveness is not clear. Therefore, in this study, we enrolled patients with early stage gastric cancer, that is stage Ia (T1N0M0), Ib (T2N0M0, T1N1M0), and only T3N0M0 out of stage IIawho are free from the effects of the aggressive nature of the tumor and the need for adjuvant chemotherapy-to evaluate the prognostic impact of the nutritional status.…”
Section: Introductionmentioning
confidence: 99%